The Influence of Rental Fees, Operating Costs, and Working Hours on Financial Behavior at the Sis Al Jufri Pearl Airport Canteen in Hammer City - Safri (Yayasan Sinergi Kawula Muda, 2025)
This research aims to analyze the influence of rental costs, operational costs and working hours on financial behavior at Mutiara Sis Al Jufri Palu airport canteen. Data was obtained from 30 respondents using a questionnaire. The analytical method used is the classic assumption test. The results of the research show that rental costs, operational costs and working hours on financial behavior simultaneously do not have a significant effect on financial behavior with a contribution of -66%. Partially, rental costs are positive and have a significant effect on financial behavior with a coefficient value of 0,055and a significance of 0,048. Operational costs also have a positive value and have a significance on financial behavior with a coefficient value of 0,031 with a significance of 0,036 and working hours have a negative value and have no a significant effect on financial behavior with a coefficient value of -0,016 and a significance of 0,352.